PENGARUH GAINSHARING DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KARYAWAN DI PT. CATUR TUNGGAL BAHANA SIDOARJO - Afifatus Sholikhah (GREENOMIKA, 2020)
In the development of an increasingly advanced business world, all companies are required to increase employee productivity considering the role of human resources is very important for the development of the company. The company must be able to build and improve from providing gainsharing and good motivation in PT. Catur Tunggal Bahana Sidoarjo. This study aims to determine the test results of the effect of gainsharing and motivation partially and simultaneously on productivity at PT. Catur Tunggal Bahana Sidoarjo. This study uses a quantitative research method using the SPSS test to measure the results of gain sharing and motivation as independent and productivity as the dependent variable. This study uses multiple regression analysis with 50 respondents with a full sampling technique of the total population. The results showed that the influence of gain sharing and motivation had a partial and simultaneous effect on productivity. So it can be concluded that gain sharing has a more dominant effect on productivity than motivation.